YANÉ RẼDÁWA TẼDÁWA SÃO FRANCISCO: arqueologia ancestral na terra indígena Tupinambá, Rio Tapajós, Amazônia - Jesus, Hudson Romário Melo de (2022)
Study was carried out among the Tupinambá people in São Francisco village and sought to reflect on and/or contribute to the knowledge of indigenous ancestry in the baixo Tapajós region, Brazilian Amazon. The use of archaeological survey methodologies was guided by the theoretical perspective of indigenous archeologies, which is grounded on contemporary archeologies and archaeological ethnographies. From these perspectives, we approach themes such as territory, meaningful places, memory, and oral tradition. The research findings were interpreted through the lens of daily life in the village and experience as an archaeologist. Archaeological dating of artifacts in Jacaré village shows that the Tupinambá territory has a long history of indigenous occupation going back 3,800 years. Likewise, the Tupinambá oral history in the Tapajós river indicates that our ancestors occupied the region before the arrival of the first Europeans. This study, therefore, deals with Tupinambá territoriality and our own interpretation of ancient pottery.